Consequences of a Criminal Record for Employment Opportunity in Milwaukee, Wisconsin, 2002 - Pager, Devah ([Verlag nicht ermittelbar], 2003)
This study examined employers' policies and practices for hiring entry-level workers in the Milwaukee metropolitan area. The study consisted of telephone interviews conducted in the spring of 2002 with 177 employers who had advertised entry-level openings in the prior six months. The survey included questions about the company, such as size, industry, employee turnover, and racial composition, questions about hiring procedures, questions about the last worker hired for a position not requiring a college degree, and questions about the employer's attitude toward various kinds of marginalized workers. An emphasis in the survey was placed on assessing employers' attitudes about and experience with applicants with criminal histories.